An experimental analysis of the topology and dynamics of a falling liquid film over the wavy surface of a vertical pillow plate. (7th July 2015) - Piper, M.; Wecker, C.; Olenberg, A.; Tran, J.M.; Kenig, E.Y.
Abstract: The successful design of pillow-plate condensers requires specific knowledge of the falling liquid film characteristics. Due to the typical wavy, "pillow-like" surface of pillow plates, the film flow here differs from the flow over vertical smooth walls. In this work, we visualized the topology and free surface waviness of a falling liquid film over a vertical pillow plate by using a fluorescent dye and a high speed camera. First observations show that the liquid film preferably flows down the rows of vertically aligned welding spots (zone 1). As a result, the wall surface between these rows is covered by a thinner film (zone 2). In order to quantify this "2-zone" topology, we measured the local mass flow rate in zone 1 over the height of the pillow plate. The results confirmed that the liquid film is mainly "drained" in zone 1. The findings of this study will help to develop flow-pattern-oriented modeling methods and to design pillow-plate falling film equipment. Abstract : Highlights: The film topology is characterized by two distinct zones. The film mainly flows down the rows of vertically aligned welding spots (zone 1). The wall region between adjacent zones 1 is covered by a thinner film (zone 2). The identified 2-zone film flow will facilitate pillow-plate heat exchanger design.